2001
DOI: 10.1016/s0014-5793(01)03098-8
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana ethylene‐responsive element binding protein (AtEBP) can function as a dominant suppressor of Bax‐induced cell death of yeast

Abstract: We identified genes based on screening of an Arabidopsis cDNA library for functional suppressors of mouse Bax-induced cell death of yeast cells. Interestingly, the cDNA encoding AtEBP, known as Arabidopsis thaliana ethyleneresponsive element binding protein, was isolated numerous times in the functional screen (82% of all suppressors). Full-length AtEBP and its localization to the nucleus were essential for the suppression of Bax-induced cell death. Morphological abnormality of intracellular network that is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…This approach is particularly useful in situations where functional screens are not experimentally well developed (e.g., plants) [27,[51][52][53]. For example, we recently reported that expression of animal antiapoptotic genes (e.g., Bcl-xL, CED-9, Op-IAP) in tobacco plants confers heritable resistance to several necrotrophic fungal and viral pathogens [54].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is particularly useful in situations where functional screens are not experimentally well developed (e.g., plants) [27,[51][52][53]. For example, we recently reported that expression of animal antiapoptotic genes (e.g., Bcl-xL, CED-9, Op-IAP) in tobacco plants confers heritable resistance to several necrotrophic fungal and viral pathogens [54].…”
Section: Discussionmentioning
confidence: 99%
“…Direct regulators and executors of PCD in plants have also been identified by their PCD suppressing activity when they are overexpressed in animals, yeasts, and plants. These include an endoplasmic reticulumassociated BAX INHIBITOR-1 (BI-1; Kawai-Yamada et al, 2001;Watanabe and Lam, 2006;Ihara-Ohori et al, 2007), a transcription factor AtEBP (Pan et al, 2001;Ogawa et al, 2005), a vesicle-associated protein VAMP (Levine et al, 2001), and an AGC kinase Adi3 (Devarenne et al, 2006). These proteins possess a diverse variety of biochemical activities and localize to different cellular compartments, suggesting the involvement of many biochemical and cellular processes in regulating or executing PCD.…”
Section: Regulation Of Cell Death and Defense By The Bap And Bon Protmentioning
confidence: 99%
“…Our finding that barley BI-1 is able to substitute for the cell death suppressor MLO as a suppressor of Bgh penetration resistance supports the idea that BI-1 inhibits a specific, although unidentified, type of endogenous plant PCD. Interestingly, besides BI-1, two antioxidants, a soybean ascorbate peroxidase and a tomato glutathione S-transferase, as well as nuclear AtEBP, a protein that is known to be ethylene responsive, are able to suppress BAX-induced cell death in yeast (32)(33)(34). Barley and Arabidopsis BI-1 genes are responsive to pathogen challenge and wounding, which are both associated with oxidative stress.…”
Section: Figmentioning
confidence: 99%